Asesmen Aspek Pengetahuan dan Teknik Penilaian melalui Penugasan Hasil Karya di TK Al-Fadillah Kelompok (B) Usia 5-6 Tahun Sleman DIY - Utia Virli Susanti (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2019)
The Knowledge aspect in the assessment is indeed very important and good if the application in the assessment process is good. In the technique of assessing aspects of knowledge of the assignment of children’s work does indeed require stages of the process, because then the teacher can understand and be able to asess well through the stages of the proess. And through permendikbud  No.146 in 2014 the teacher can she the KD and indicators that can be developed in the learning process, so that the child will be well stimulated with the learning process with the theme  stages every month. The research method used by the author through qualitative research, from this qualitative research the author knows that reality is meaningful in this study as what and here the author does the technique of collecting observation data through interviews and documentation. From the interview the author was given the apportunity to speak to one of the teachers in class B, and at that time the outhor knew the reality that existed in the school  and the author obtained documentation from the resultsof the teacher’s assessment of the child at each stage of the assessment. Some of the journals that I get and the authors see in fact in the field do look the same, but that are differences in the development of themes that Al-Fadilah kindergarten uses according to the needs of children, and more around children so children will understand it directly, and because provide an opportunity for each school institution to develop an existing curriculum. And it turnet out that in Al-Fadilah the curriculum had been developed and made it easier forteachers in the teaching process.       Keywords: Assessment, aspects of knowledge, work.